Total flavonoids, phenolics, tannins and antioxidant activity in seeds of lentil and grass pea - Dibyendu Talukdar, (International Journal of Phytomedicine, 2012)
Lentil (Lens culinaris Medik.) and grass pea (Lathyrus sativus L.) are rich in polyphernols and antioxidants and in constant use as food and nutritional supplements in many traditional diets throughout the world. Both plants reportedly possess beneficial effects in jaundice, high fever, measles, diabetes, and cardiac problem. Despite immense potentiality, limited work was done regarding antioxidant potential in different genotypes of these two legumes, useful in phytomedicinal and pharmacological formulations. The objective of the present study was to assess the antioxidant composition and activity of ethanolic extract (ethanol: water, 80:20 v/v) of seeds (edible grain) of three improved genotypes each in lentil and grass pea. Total phnolics and flavonoids were estimated by the Folin–Ciocalteu colorimetric method and aluminium chloride method, respectively. Condensed tannin (pro anthocyanidins) content was determined using leucocyanidin (LE) equivalent. Antioxidant activity was ascertained by different in vitro protocols such as DPPH, β-carotene bleaching assay, reducing power and free radical scavenging activity. Among the genotypes, IPL 406 in lentil and BioL 212 in grass pea showed the best performance with highest phenolic and flavonoid content and superior antioxidant activity as evidenced in potential FRAP, bleaching assay and by the low IC50 values in DPPH, hydroxyl and superoxide radical scavenging assay compared to WBL 58 and B 256 in lentil and B1 and BioR 231 in grass pea. The six genotypes differed significantly (P < 0.05) in antioxidant content and activity. Both legumes are potential enough as phytomedicinal and functional foods with ample scope for genotype-wise phyto-nutrient profiling.